Prevention of Cyclophosphamide-Induced Immunosuppression in Mice With Traditional Chinese Medicine Xuanfei Baidu Decoction - Yan, Huimin; Lu, Jia; Wang, Jiabao; Chen, Lu; Wang, Yu; Li, Lin; Miao, Lin; Zhang, Han (Frontiers in Pharmacology, 2021)
Background and aims: Xuanfei Baidu decoction (XFBD), a traditional Chinese medicine formulation, was designed and successfully applied for COVID-19 disease treatment in China, while the mechanism is still not clear. Methods: To evaluate the protective effect of XFBD on immunosuppression in cyclophosphamide (CY)-treated mice, XFBD was orally administrated, the body weight was measured, and the immune organ index was calculated. HE staining was performed to analyze the pathological structures of the liver, spleen, and thymus. The levels of cytokines and immunoglobulin in the serum and spleen were evaluated by ELISA and RT-PCR. Splenic lymphocytes were isolated, and LPS-stimulated cell proliferation and the number of CD4+ and CD8+ T lymphocytes were evaluated. Results: XFBD significantly suppressed body weight loss and increased the indices of spleen and thymus. The pathological alteration was much improved after XFBD administration. The reductions of TNF-α, IFN-γ, IgG, and IgM levels in serum and IL-2, IL-4, and IL-6 expressions in the spleen were all significantly alleviated by XFBD. Splenic lymphocyte proliferation in response to LPS was further enhanced after treatment with XFBD. The reduction of CD4+ and CD8+ T lymphocytes in CY-treated mice was also highly increased in XFBD groups. Conclusion: Our findings suggested that XFBD played a crucial role in protection against immunosuppression in CY-treated mice and could be a potential candidate for immune modification and therapy.